2018
DOI: 10.1155/2018/3726091
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Methylation of FBP1 Gene in Non-Small Cell Lung Cancer

Abstract: Because NSCLC has poor overall prognosis and is frequently diagnosed at later stage, we aimed to seek novel diagnosis biomarkers or therapy target of the disease in this study. Fructose-1,6-bisphosphatase 1 (FBP1) is a rate-limiting enzyme in gluconeogenesis, which was usually lost in NSCLC due to abnormal methylation in promoter DNA sequence. The clinical data indicated that the methylation rate in FBP1 gene promoter was negatively related to the overall survival of the NSCLC patients. DNA methylation transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…EZH2, the critical element of a methyltransferase named polycomb repressive complex 2 (PRC2) 31 , could serve as a master regulator of transcription that contributes to cancer development and progression via promoter hypermethylation of target gene 32 . Interestingly, transcriptional inactivation of FBP1 expression due to promoter region DNA hypermethylation was observed in hepatocellular carcinoma 25 , colon cancer 33 , gastric carcinogenesis 34 , basal-like breast cancer 24 and lung cancer 35,36 . Furthermore, recent studies have reported that epigenetic modifications like DNA and histone methylation could exhibit functional cooperation in heritable repression of gene activity 3740 .…”
Section: Resultsmentioning
confidence: 99%
“…EZH2, the critical element of a methyltransferase named polycomb repressive complex 2 (PRC2) 31 , could serve as a master regulator of transcription that contributes to cancer development and progression via promoter hypermethylation of target gene 32 . Interestingly, transcriptional inactivation of FBP1 expression due to promoter region DNA hypermethylation was observed in hepatocellular carcinoma 25 , colon cancer 33 , gastric carcinogenesis 34 , basal-like breast cancer 24 and lung cancer 35,36 . Furthermore, recent studies have reported that epigenetic modifications like DNA and histone methylation could exhibit functional cooperation in heritable repression of gene activity 3740 .…”
Section: Resultsmentioning
confidence: 99%
“…Fructose‐1,6‐bisphosphatase (Fbp1) is a rate‐limiting enzyme of gluconeogenesis that catalyses the splitting of fructose‐1,6‐bisphosphate into fructose 6‐phosphate and inorganic phosphate 8 . Fbp1 reportedly plays a critical role in several diseases, including type 2 diabetes mellitus, 9 cancers 10‐12 and acute liver failure 13 . Kaur et al 9 reported that Fbp1 can be considered a potential target for the treatment of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…In another study in the H460 large cell lung cancer cell line, silencing FBP1 significantly increased cellular proliferation and migration. 29 Therefore, FBP1 seems to consistently act as a tumor suppressor in different types of lung cancer.…”
Section: Discussionmentioning
confidence: 99%